From Norm- referenced to Criterion-referenced Instructional Assessment in an ESL classroom - Kteish, Irena (Beirut Ligue des Professeurs de l'U.L, 2010)
Analysis of standards of professional knowledge and competence in the field of instructional assessment suggests that there has been an increasing improvement in specification of knowledge and skills indispensable for educators to apply assessment techniques effectively and appropriately for concrete instructional objectives and T/L variables. However, the author seeks a more balanced synthesis of traditional and alternate assessment techniques within a communicative second language framework. The paper has demonstrated that the process of specification of performance criteria is a multi-step procedure which requires a special skill on behalf of educators. Improving criterion-referenced assessment has been a priority in recent years, but it is still a challenging issue to be faced because in each concrete T/L context educators are expected to be skilled in developing criterion-referenced instruments of assessments appropriate for the concrete T/L situations by themselves.
(3GdfhY (B: Articles
Keywords: English Language Education School Evaluation; L$1 (Benseignement de la Langue Anglaise Evaluation Scolaires; (3JYdje GddZI GdGfcdjRjI GdJbjje GdeOQSjs